Uma proposta de modelagem matem?tica para tratamento de tr?fego com caracter?stica auto-similar - Prata J?nior, Oscavo Gonzaga (2004)
The tra c models applied in the past for design and performance analysis of the telephony networks became ine cient due to the change in the statistical nature of data tra c. This instigate the scienti c/academic community to looks for models that are capable to treat that new characteristic statistics of the tra c. This document presents a proposal of mathematical model capable to represent the self{similar feature of the tra c of the current networks. The intended model uses the Pareto distribution with Hurst parameter to characterize the package interarrival time. Consequently, it is presented the relevant for variable of location for Pareto distribution modelling self{similar tra c. We also present a study using the proposed model for classic queue theory .